Penerapan Persidangan Elektronik (E-Litigation) Dalam Penyelesaian Sengketa di Peradilan Tata Usaha Negara - Dao, Fiktorius Kehidupan (Universitas Medan Area, 2025)
The State Administrative Court (PTUN) is the judicial authority authorized to examine, decide, and resolve cases deemed to constitute state administrative disputes, including petitions related to the scope of the administrative court's jurisdiction. In line with advances in information technology and the demands of simple, expeditious, and low-cost judicial principles, the Supreme Court of the Republic of Indonesia has implemented an electronic-based judicial system through E-Court and E-Litigation. This study aims to analyze the application of electronic trials in dispute resolution at the PTUN and examine the validity of electronic evidence in court practice. The research method used is normative juridical law, utilizing statutory and conceptual approaches. The results indicate that the implementation of electronic trials at the PTUN has a sufficient legal basis, normatively, through Supreme Court Regulation Number 1 of 2019. However, in practice, obstacles remain, particularly related to the authentication and assessment of electronic evidence and limited internet network infrastructure in some regions. Therefore, strengthening the electronic evidence verification mechanism and improving infrastructure support are necessary to ensure the effectiveness and legal certainty in the administration of electronic-based state administrative courts.